Modifiable risk factors for patients undergoing lung cancer surgery and their optimization: a review - Gagné, Sylvain; McIsaac, Daniel I. (Journal of Thoracic Disease, 2018)
Enhanced recovery after surgery (ERAS) programs include a variety of pre-, intra- and post-operative interventions that seek to decrease the stress response to surgery and facilitate the recovery of surgical patients. There are a number of patient factors that may increase the risk of postoperative complications (POC) after lung cancer surgery and delay recovery. Some of these factors may be amenable to optimization preoperatively and potentially decrease the incidence of these complications. We have chosen to discuss the incidence and complications associated with factors we felt were both relatively common and significant contributors to POCs. For each of these factors we discuss potential avenues for optimization and the evidence for the resulting decrease in complications.